1989
DOI: 10.1016/s0022-5347(17)41030-5
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Treatment of Stages T2 to T4 Bladder Cancer with Cis-Platinum, Cyclophosphamide and Doxorubicin

Abstract: In an ongoing phase II study 17 patients with potentially operable transitional cell carcinoma of the bladder (stages T2 to T4, Nx, Mo) have been treated with intravenous cis-platinum (50 mg.per m.2), cyclophosphamide (400 mg.per m.2) and doxorubicin (40 mg.per m.2). They were to receive 3 treatments at 3-week intervals before cystectomy and 2 treatments at 3-week intervals commencing 5 weeks after cystectomy. Of 17 patients 14 (82 per cent) completed all 3 preoperative treatments but only 7 (41 per cent) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Cisplatin was well tolerated and did not present problems with administration in the context of a large multicentre trial; 12% did not receive a second course of cisplatin, which is comparable to the 13% who did not receive preliminary chemotherapy in the study reported by Shearer et al (1988) and18% reported by McCullough et al (1989); 85% of the West Midlands patients received a third course with 10% having a reduced dose. Neither study attempted any maintenance chemotherapy, which was attempted by both Shearer et al (1988) andMcCullough et al (1989), with only 59 and 41% receiving their maintenance chemotherapy. Long courses of adjuvant chemotherapy cannot be given to h e majority of patients with invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin was well tolerated and did not present problems with administration in the context of a large multicentre trial; 12% did not receive a second course of cisplatin, which is comparable to the 13% who did not receive preliminary chemotherapy in the study reported by Shearer et al (1988) and18% reported by McCullough et al (1989); 85% of the West Midlands patients received a third course with 10% having a reduced dose. Neither study attempted any maintenance chemotherapy, which was attempted by both Shearer et al (1988) andMcCullough et al (1989), with only 59 and 41% receiving their maintenance chemotherapy. Long courses of adjuvant chemotherapy cannot be given to h e majority of patients with invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recently reported neoadjuvant chemotherapy for patients with advanced bladder Cancer, regimens using M-VAC (methotrexate, vinblastine, doxorubicin and cisplatin), CISCA (cyclophosphamide, doxorubicin and cisplatin) or CMV (cisplatin, methotrexate and vinblastine) are widely used. The respective response rates are summarized as follows: M-VAC induced 24 % cCR and 27 % cPR by TUR in 50 patients with T 2 _ 4 N 0 M 0 tumors(Scher et al, 1988); CISCA 0% pCR and 53 % pathological down-staging or greater than 50% reduction of tumor volume in 17 patients with T2-4N x Mo tumors(McCullough et al, 1989); CMV 10% pCR, 49% pathological downstaging and 41 % no change in 44 patients with T3-4N0/ N( + )Mo tumors (Mafezzini et al, 1991).…”
mentioning
confidence: 99%